A comparison of two global positioning system devices for team-sport running protocols - Willmott, A. G. B.; James, C. A.; Bliss, A.; Leftwich, R. A.; Maxwell, N. S. (Journal of Biomechanics, 2019)
The comparability and reliability of global positioning system (GPS) devices during running protocols associated with team-sports was investigated. Fourteen moderately-trained males completed 690 m of straight-line movements, a 570 m change of direction (COD) course and a 642.5 m team-sport simulated circuit (TSSC); on two occasions. Participants wore a FieldWiz GPS device and a Catapult MinimaxX S4 10-Hz GPS device. Typical error of measurement (TE) and coefficient of variation (CV%) were calculated between GPS devices, for the variables of total distance and peak speed. Reliability comparisons were made within FieldWiz GPS devices, between sessions. Small TE were observed between FieldWiz and Catapult GPS devices for total distance and peak speed during straight-line (16.9 m [2%], 1.2 km·h-1 [4%]), COD (31.8 m [6%], 0.4 km·h-1 [2%]) and TSSC protocols (12.9 m [2%], 0.5 km·h-1 [2%]), respectively, with no significant mean bias (p > 0.05). Small TE were also observed for the FieldWiz GPS device between sessions (p > 0.05) for straight-line (9.6 m [1%], 0.2 km·h-1 [1%]), COD (12.8 m [2%], 0.2 km·h-1 [1%]) and TSSC protocols (6.9 m [1%], 0.6 km·h-1 [2%]), respectively. Data from the FieldWiz GPS device appears comparable to established devices and reliable across a range of movement patterns associated with team-sports.